A review of competitive sport motivation research - Clancy, R. B.; Herring, M. P.; MacIntyre, T. E.; Campbell, M. J. (Psychology of Sport and Exercise, 2016)
Objectives: The purpose of this review was to synthesise contemporary research on competitive sport motivation (1995-2016) with a view to identifying trends and gaps in sample characteristics, research designs and analytical strategies, and classifying associated topics. Design: Narrative review. Method: Four databases were searched using a focused search strategy, leading to 63 studies that met the inclusion criteria. These were then evaluated in five sections: Theoretical Frameworks, Sample Characteristics, Research Designs, Analytical Strategies and Topics. Results: A total of 63 studies comprising 12,440 participants were appraised. The average sample size and participant age were 197 and 22.6 years, respectively. Just over half of the studies described their sample as high-level. The majority of studies were quantitative and employed a cross-sectional design. A range of innovative statistical analyses were used, with structural equation modelling being increasingly adopted. In addition to studies focusing on motivation as a stand-alone topic, researchers in the area also investigated its relationship with motivational climate, burnout, doping, perfectionism, injury, and several other related variables. Conclusions: After reviewing the body of research on this specific topic area, promising directions for future research are presented. The focused approach particularly seeks to encourage researchers to employ different methodologies, and prioritise underused topics in future research on competitive athlete groups. Furthermore, the review points to several practical implications for competitive sport stakeholders.